2019
DOI: 10.1021/acs.iecr.9b02164
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Porous and Water-Tolerant Metal–Organic Frameworks for Enzyme Encapsulation

Abstract: Metal−organic frameworks (MOFs) for in situ enzyme encapsulation commonly possess weak metal−ligand coordination bonds and rather small pores, which are instable in aqueous solution and present rather high diffusion resistance of reactants. Herein, we prepare a type of hierarchically porous and water-tolerant MOFs through a facile polyphenol treatment method for enzyme encapsulation. In brief, enzymes are first in situ encapsulated in a zeolitic imidazolate framework-8 (ZIF-8) through coprecipitation of enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 43 publications
3
34
0
1
Order By: Relevance
“…SEM showed that GOx@ZIF‐8 was smaller than ALP@ZIF‐8 in particle size. The shape of these composites was similar to those reported in some studies [15,18,24] but different from the polyhedral shape reported in others [5,7,8] . The variations in morphology ( e. g .…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…SEM showed that GOx@ZIF‐8 was smaller than ALP@ZIF‐8 in particle size. The shape of these composites was similar to those reported in some studies [15,18,24] but different from the polyhedral shape reported in others [5,7,8] . The variations in morphology ( e. g .…”
Section: Resultssupporting
confidence: 70%
“…It is therefore likely that the susceptibility of enzyme@ZIF‐8 composites to these chemical agents is not greatly affected by the exact nature of the proteins in the composites. However, the morphology, particle size and crystallinity of the enzyme@ZIF‐8 composites do appear to vary among studies even under similar synthesis conditions [5,7,8,15,18,24] and surface area of lipase@ZIF‐8 is affected by the Zn 2+ /2‐MI molar ratio during synthesis [61] . It is likely that these properties ( i. e .…”
Section: Resultsmentioning
confidence: 98%
“…[21,38] Compared to the previous methods, [31][32][33][34][35][36] this method is facile,l ow-cost, and less-time consuming.Importantly,itiscompatible with most substrates because of the high binding affinity of TA to diverse surfaces, which has shown potential as ah ost platform for enzyme immobilization. [39] However, the complex interfacial interactions of enzyme and hierarchically porous MOFs are rarely revealed. Very recently,T sung and co-workers probed the interactions between encapsulated enzyme and hollow-shell MOF matrices.…”
Section: Introductionmentioning
confidence: 99%
“…[83] Electrostatic interaction between GOx/PCN-222(Fe) GOx/PCN-222(Fe) stable at pH 27. [84] Surface coating Tannic acid coating on MOFs ZIF-8@ZnTA remained stable at pH 5.0 for 1 h. [86] Silanes or coordination complexes (TA and Fe 3+ ) SiO 2 @catalase/ZIF-8 and Fe 3+ -TA@catalase/ZIF-8 remained stable at pH 3.0 for 60 min. [87] Defect engineering Inserting carboxylate or phosphate-rich biomacromolecules PGA@ZIF-L, DNA@ZIF-L and catlase@ZIF-L remained stable at pH 5 for 3 h. [88] Synergistic properties…”
Section: Creating Hollow Cavitiesmentioning
confidence: 99%